2022
DOI: 10.35784/pe.2022.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Green Economy – Vector of Sustainable Development

Abstract: The article is devoted to the formation of theoretical, methodological foundations and the development of conceptual approaches to the practical provision of the green economy, considered as a vector of sustainable development. The study substantiates the need to create a new global economic school. The existence of two concepts of economic development of future generations is established. The author’s vision of economic growth in the conditions of sustainable development is formed, as well as its necessity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
0
5
0
4
Order By: Relevance
“…This thesis is confirmed by the results obtained from the analysis of energy efficiency of spring wheat production which demonstrates that conventional tillage contributes to increased production costs (e.g. fuel inputs are about 30% higher than for conservation tillage) [21,[26][27][28][29][30][31][32]. Therefore, conservation tillage combined with cultivation of white mustard as a catch crop can be tentatively recommended to be applied in agricultural practice.…”
Section: Specificationmentioning
confidence: 54%
“…This thesis is confirmed by the results obtained from the analysis of energy efficiency of spring wheat production which demonstrates that conventional tillage contributes to increased production costs (e.g. fuel inputs are about 30% higher than for conservation tillage) [21,[26][27][28][29][30][31][32]. Therefore, conservation tillage combined with cultivation of white mustard as a catch crop can be tentatively recommended to be applied in agricultural practice.…”
Section: Specificationmentioning
confidence: 54%
“…At the same time, the concept of green development has penetrated into all walks of life, promoting the green technology innovation of enterprises to assume environmental responsibility. Ospanova et al proposed a component model of sustainable development that could reflect the essence and content of green economy, which summarized the positive experiences of green integration [ 71 ]. Lam et al aimed to investigate the green marketing status of major ports in the world and suggested that ports should link the three basic aspects of strategy, structure and function in green marketing [ 72 ].…”
Section: Evolution Of Research Themes and Trendsmentioning
confidence: 99%
“…Masing-masing menerjemahkan secara berbeda namun memiliki substansi yang sama. Ada beberapa pengertian Green economy yang dikemukakan oleh ahli, antara lain (Ospanova et al, 2022): Green economy adalah ekonomi yang harus membantu kebijakan lingkungan. David Pierce, Edward Barbier and Enil Markandia.…”
Section: Definisi Green Economyunclassified
“…Kata kunci: Green economy; pembangunan; lingkungan dan sustainaibility PENDAHULUAN Studi terkait Green economy umumnya dikaitkan dengan pembangunan berkelanjutan (misal: Ali et al, 2021;Kasztelan, 2017;Mikhno et al, 2021aMikhno et al, , 2021bOspanova et al, 2022). Saat ini, pembangunan berkelanjutan merupakan target capaian global yang secara kolektif ingin dicapai setiap negara lewat program SDGs (Sustainable Development Goals).…”
unclassified